Harmonic Analysis of Multipath Index Time Series in GPS Stations† - Souza, E.m.; Alves, D.b.m.; Schumacher, F.l. (Sociedade Brasileira de Matemática Aplicada e Computacional, 2015)
The identification of the cyclical and seasonal variations can be very important in time series. In this paper, the aim is to identify the presence of cyclical or seasonal variations in the indices of the multipath effect on continuous GPS(Global Positioning System) stations. Due to the model used to obtain these indices, there should not have cyclical variations in these series, at least due to the multipath effect. In order to identify the presence of cyclical variations in these series, correlograms and Fourier periodograms were analyzed. The Fisher test for seasonality was applied to confirm the presence of statistical significant seasonality. In addition, harmonic models were adjusted to check in which months of the year the cyclical effects are occurring in the multipath indices. The possible causes of these effects are pointed out, which will direct the upcoming investigations, as well as the analysis and correlations of other series. The importance of this analysis is mainly due to the fact that errors in the collected signals of these stations will directly influence the accuracy of the results of the whole community that directly or indirectly uses GPS data.

A identificação de variações cíclicas e sazonais é muito importante em séries temporais. Neste artigo, objetiva-se identificar a presença de variações cíclicas e sazonais nos índices do efeito do multicaminho em estações GPS (GlobalPositioning System) de monitoramento contínuo. Devido ao modelo usado na obtenção de tais series, não deveriam existir variações cíclicas nas mesmas, pelo menos devido ao multicaminho. No sentido de identificar a presença de variações cíclicas nestas séries, foram analisados correlogramas e periodogramas de Fourier. Para confirmar a presença de sazonalidade estatisticamente significativa, foi utilizado o teste de Fisher para sazonalidade. Além disso, modelos harmônicos foram ajustados para verificar em que meses do ano os picos dos efeitos cíclicos estão ocorrendo. As possíveis causas dos efeitos são apontadas, as quais direcionarão investigações futuras, bem como a análise e correlações com outras séries. A importância desta análise se deve principalmente ao fato de que erros nos sinais coletados afetarão a acurácia dos resultados de toda a comunidade que usam dados GPS diretamente ou indiretamente.
Keywords: harmonic analysis; multipath index; time series; análise harmônica; índice de multicaminho; séries temporais